Pengaruh Perilaku Hidup Sehat dan Literasi KMS terhadap TUMBANG Balita - Faik Agiwahyuanto; Dyah Ernawati; Evina Widianawati (Jurnal Kesehatan, 2021)
The growth and development status of children was been seen from nutritional status andcognitive and psychomotor aspects of children aged 0 to 5 years and child will automaticallyfollow behaviour of their parent’s lives. Aside from being a source of child healthinformation, in the KMS book there was also information on children's weight and heightgraphic data obtained from the Posyandu scales. To determine the influence of healthy livingbehaviors of parents and KMS book, literacy towards the growth and development status ofbabies-toddlers. The study design was correlative with the type of cross-sectional study, thethe sample was 49 respondents, data collection techniques used healthy life behaviorquestionnaires and KMS book literacy and observations and records from the results ofmeasurements of growth and development status of infants-toddlers in January 2020, anddata analysis using Pearson Correlation test. The healthy behavior of parents and KMS bookliteracy influenced the growth and development status babies-toddlers. The cognitive aspectsof the community were able to read the KMS chart and find out the meaning of the KMSchart to monitor the weight and nutritional status of babies-toddlers. In the psychomotoraspect, people began to realize the importance of giving breast milk for >6 months andcooking their own food. The suggestion was need for more intensive mentoring to Posyanduadministrators to increase KMS literacy and be able to teach it to all families.